2007
DOI: 10.3989/ajbm.2007.v64.i2.167
|View full text |Cite
|
Sign up to set email alerts
|

The systematic position of <i>Cubanthus</i> and other shrubby endemic species of <i>Euphorbia</i> (Euphorbiaceae) in Cuba

Abstract: Cubanthus (Euphorbiaceae) has traditionally been recognized as a small genus of three similar species restricted to Cuba and Hispaniola. In this study we used DNA sequence data from the nuclear ITS and chloroplast ndhF gene regions to investigate its systematic position and the position of four other shrubby Euphorbia species endemic to Cuba: E. cubensis, E. helenae, E. munizii, and E. podocarpifolia. The results demonstrate that all of these taxa belong to a well-supported Antillean clade nested within Euphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…are either paraphyletic or polyphyletic. Further work (Steinmann 2003;Bruyns et al 2006;Steinmann et al 2007;Zimmermann et al 2010;Horn et al 2012) confirmed and extended these findings, and led to the broadly construed generic concept of Euphorbia that is gaining increasing acceptance. Steinmann and Porter (2002) also recovered four major lineages within Euphorbia, designated as clades A-D; with one exception, these do not correspond to any previously known taxon but are composed of various sections or subgenera of Euphorbia; only a single clade, by and large, is congruent with subg.…”
Section: Key T O T H E Tribes O F Subfam Euphorbioi-supporting
confidence: 52%
“…are either paraphyletic or polyphyletic. Further work (Steinmann 2003;Bruyns et al 2006;Steinmann et al 2007;Zimmermann et al 2010;Horn et al 2012) confirmed and extended these findings, and led to the broadly construed generic concept of Euphorbia that is gaining increasing acceptance. Steinmann and Porter (2002) also recovered four major lineages within Euphorbia, designated as clades A-D; with one exception, these do not correspond to any previously known taxon but are composed of various sections or subgenera of Euphorbia; only a single clade, by and large, is congruent with subg.…”
Section: Key T O T H E Tribes O F Subfam Euphorbioi-supporting
confidence: 52%
“…Macaronesicae and occur in the Antilles and the Bahamas [ Euphorbia subgenus Euphorbia section Cubanthus ; see Steinmann et al . () and Dorsey et al . ()], Malesia‐Melanesia‐Australia [ E. plumerioides , placed in Euphorbia subgenus Euphorbia section Pacificae ; see Forster () and Dorsey et al .…”
Section: Soft‐wooded Shrubby Spurges: Their Horticultural Valuementioning
confidence: 87%
“…These other groups are phylogenetically distant from subsect. Macaronesicae and occur in the Antilles and the Bahamas [Euphorbia subgenus Euphorbia section Cubanthus; see Steinmann et al (2007) and Dorsey et al (2013) Chevalier (1935), Carter et al (1984), Brochmann & Rustan (1987), Brochmann et al (1997), Gomes et al (1995), and Duarte & Moreira (2002). The species occurs throughout Cabo Verde except on the island of Maio and the islets of Branco and Raso (Fig.…”
Section: Soft-wooded Shrubby Spurges: Their Horticultural Valuementioning
confidence: 99%
“…Euphorbia. Likewise, Pedilanthus (Steinmann, 2002;Park & Jansen, 2007) and Cubanthus (Steinmann et al, 2007) should also be included in Euphorbia s.l. The alternative to the sinking of all these well-established segregates (each conforming to a more or less monophyletic clade) would be to break up Euphorbia s.l.…”
Section: No Tes O N Selec Ted Familiesmentioning
confidence: 99%